EVALUATION THE LECTURER PERFORMANCE (BE REVIEWED FROM CERTIFICATION AND WORK EXPERIENCE IN STATE INSTITUTE FOR ISLAMIC STUDIES SULTHAN THAHA SAIFUDDIN JAMBI) - ZUHRI, FIRDAUS (PPs UNJ, 2015)
The purpose of this research is in order to know the lecturer performance be reviwed from certification and work experience in State institute for islamic studies Sulthan Thaha Saifuddin Jambi. Researcher in conducting this research , causal comparative / expost-facto and (Two Way Analisis of Variance)factorial 2 x 2 as statistikal analysis method for improving cause and effect variables relationship. The hypothesis were built that Certification, work experience impact the lecturer performance. Technic sample was used random sampling upon 96 lecturers as respondents. The result of this research proved that certification, work experience imfacted the lecturer performance.